2020
DOI: 10.1101/2020.02.13.948760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tol-Pal system and Rgs proteins interact to promote unipolar growth and cell division inSinorhizobium meliloti

Abstract: 19Sinorhizobium meliloti is an -proteobacterium belonging to the Rhizobiales. Bacteria from this 20 order elongate their cell wall at the new cell pole, generated by cell division. Screening for protein 21 interaction partners of the previously characterized polar growth factors RgsP and RgsM, we 22 42 knowledge of components of the polarly localized machinery driving cell wall growth and suggest 43 a complex of Rgs proteins with components of the divisome, differing in composition between 44 the polar cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Apolipophorins and related Apolipoproteins are characterized by structurally flexible bundles of amphipathic α-helices that undergo conformational changes (SI Appendix, Fig. S1C) to mediate lipid interactions in eukarya (33)(34)(35), but related domains are also found in other large bacterial coiled-coil proteins (SI Appendix, Table S1) (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Apolipophorins and related Apolipoproteins are characterized by structurally flexible bundles of amphipathic α-helices that undergo conformational changes (SI Appendix, Fig. S1C) to mediate lipid interactions in eukarya (33)(34)(35), but related domains are also found in other large bacterial coiled-coil proteins (SI Appendix, Table S1) (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of a set of S. meliloti genes related with the synthesis of the lipid A, the core polysaccharide and the O-antigen of LPS (acpXL,lpxXL,lpxK,ddhAB,kdsB,kdtA,lpsB,lpsCE,lpsS) (Lagares et al, 2001;Sharypova et al, 2003), as well as the lsrB gene that codes for a transcriptional regulator that activates the expression of LPS biosynthetic genes (Tang et al, 2014), were found to be up-regulated during predation. Likewise, the periplasmic TolB1 and the OM-anchored Pal lipoprotein, which are elements of the Tol/Pal system known to contribute to cell envelope integrity (Krol et al, 2020;Szczepaniak et al, 2020), showed increased expression. It was also remarkable that several genes involved in membrane lipid synthesis were upregulated (Figures 4A, B).…”
Section: Drastic Changes In the S Meliloti Cell Envelope During Preda...mentioning
confidence: 99%